MISI PENDIDIKAN SPIRITUAL KENABIAN NABI MUHAMMAD (Analisis Ikhtiar Membentuk Karakter Anak Bangsa Dengan Pendekatan Hikmah) - Syarif Syarif (The Pontianak State Institute of Islamic Studies, 2011)
Education in the Islamic world, the real figure should appear Muhammad as the leading and most successful educators. But Muhammad did not appear today. Muhammad was especially touched by the mission in the practice of the educational process which is attributed to Islam except just touched in discourse without end. It happened because the essence of the mission of Muhammad is not understood. Missi Muhammad actually just about